Penerapan Metode Eklektik (Metode Drill dan Metode Reward and Punishment) untuk Meningkatkan Motivasi dan Hasil Belajar Mufradat Siswa Kelas VII A MTs. Al-Islam - Muhammad, Darsa; Susiani, Ika Wahyu (Universitas KH. Mukhtar Syafaat, 2026)
The drill method that is commonly used by teachers in Class VII A of Al-Islam Joresan Junior High School in fact becomes less effective during the day, because on average students have experienced boredom and boredom in learning when the weather conditions are hot and the physical condition is tired. This condition makes the motivation and learning outcomes of the students very low. Only 10 students out of a total of 28 students in the class had their mufradat memorization scores reaching the Minimum Completeness Criteria. Therefore, the researcher tried to collaborate the drill method that is commonly used in the school with the Reward and Punishment method in the classroom to increase the motivation and learning outcomes of the students. The application of the combined method between the two, which is better known as the eclectic method, is expected to increase the students' enthusiasm for learning so that their learning outcomes also increase. This research is included in the class action research. The researcher carried out two cycles to improve student motivation and learning outcomes. Each cycle consists of planning, implementation, observation, and reflection. Data collection is carried out through observation and test techniques. The analysis technique uses qualitative and quantitative data analysis. The results of this study show that the motivation to learn mufradat of Class VII A of Al-Islam Joresan Junior High School students increased. There were no students who were sleepy when the learning took place, the majority of them scrambled to answer questions about mufradat from the teacher. Their learning outcomes have increased in cycles I and II. The number of students who achieved the Minimum Completeness Criteria score in the pre-cycle was only 35.7%, in the first cycle it increased to 67.8% and increased to 92.8% in the second cycle.